MRI Assessment of Treatment Response in HIV‐associated NAFLD: A Randomized Trial of a Stearoyl‐Coenzyme‐A‐Desaturase‐1 Inhibitor (ARRIVE Trial). Issue 5 (18th June 2019) - Ajmera, Veeral H.; Cachay, Edward; Ramers, Christian; Vodkin, Irine; Bassirian, Shirin; Singh, Seema; Mangla, Neeraj; Bettencourt, Richele; Aldous, Jeannette L.; Park, Daniel; Lee, Daniel; Blanchard, Jennifer; et al.
Abstract : Aramchol, an oral stearoyl‐coenzyme‐A‐desaturase‐1 inhibitor, has been shown to reduce hepatic fat content in patients with primary nonalcoholic fatty liver disease (NAFLD); however, its effect in patients with human immunodeficiency virus (HIV)–associated NAFLD is unknown. The aramchol for HIV‐associated NAFLD and lipodystrophy (ARRIVE) trial was a double‐blind, randomized, investigator‐initiated, placebo‐controlled trial to test the efficacy of 12 weeks of treatment with aramchol versus placebo in HIV‐associated NAFLD. Fifty patients with HIV‐associated NAFLD, defined by magnetic resonance imaging (MRI)–proton density fat fraction (PDFF) ≥5%, were randomized to receive either aramchol 600 mg daily (n = 25) or placebo (n = 25) for 12 weeks. The primary endpoint was a change in hepatic fat as measured by MRI‐PDFF in colocalized regions of interest. Secondary endpoints included changes in liver stiffness using magnetic resonance elastography (MRE) and vibration‐controlled transient elastography (VCTE), and exploratory endpoints included changes in total‐body fat and muscle depots on dual‐energy X‐ray absorptiometry (DXA), whole‐body MRI, and cardiac MRI. The mean (± standard deviation) of age and body mass index were 48.2 ± 10.3 years and 30.7 ± 4.6 kg/m 2, respectively. There was no difference in the reduction in mean MRI‐PDFF between the aramchol group at –1.3% (baseline MRI‐PDFF 15.6% versus end‐of‐treatment MRI‐PDFF 14.4%, P  = 0.24) and the placebo group at –1.4% (baseline MRI‐PDFF 13.3% versus end‐of‐treatment MRI‐PDFF 11.9%, P  = 0.26). There was no difference in the relative decline in mean MRI‐PDFF between the aramchol and placebo groups (6.8% versus 1.1%, P  = 0.68). There were no differences in MRE‐derived and VCTE‐derived liver stiffness and whole‐body (fat and muscle) composition analysis by MRI or DXA. Compared to baseline, end‐of‐treatment aminotransferases were lower in the aramchol group but not in the placebo arm. There were no significant adverse events. Conclusion : Aramchol, over a 12‐week period, did not reduce hepatic fat or change body fat and muscle composition by using MRI‐based assessment in patients with HIV‐associated NAFLD (clinicaltrials.gov ID:NCT02684591).